Penerapan model pembelajaran group investigation untuk meningkatkan kemampuan berpikir kreatif matematika - Ni Made Raony Vigraha Swari (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
This research is a classroom action research that aims to find out whether the application of the Group Investigation learning model can improve students' mathematical creative thinking abilities. The preliminary data of mathematical creative thinking ability was obtained from the results of daily math tests in pre-cycle, which showed that the class XII MIPA 3 had the lowest level of creative thinking ability compared to other classes with a percentage of 32.05% creative thinking ability level that was classified as less creative, with an average of 63.98 below the minimum completeness criteria of 65. Therefore, the chosen research subjects were students of class XII MIPA 3 odd semester 2018/2019, totaling 40 people at SMAN 2 Kuta. The object of this study is the ability of students to think creatively in Limit Trigonometry. Data on students' mathematical creative thinking skills were collected using a mathematical description test and analyzed descriptively qualitatively. This research is said to be successful if the students' creative mathematical thinking ability is at least a creative category. After calculating the results obtained have increased in cycles I and II respectively 51.39% and 71.39%. If classified as creative thinking abilities, the first cycle is classified as quite creative, while the second cycle is classified as creative, so the action is considered successful. The conclusion that the application of the Group Investigation learning model can improve the ability to think creatively in mathematics. Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk mengetahui apakah penerapan model pembelajaran Group Investigation dapat meningkatkan kemampuan berpikir kreatif matematika siswa. Data awal kemampuan berpikir kreatif matematika diperoleh dari hasil ulangan harian matematika pada pra siklus, yang menunjukkan bahwa kelas XII MIPA 3 memiliki tingkat kemampuan berpikir kreatif paling rendah dibandingkan kelas lainnya yaitu dengan persentase tingkat kemampuan berpikir kreatif 32,05% yang tergolong kurang kreatif, dengan rata - rata 63,98 di bawah kriteria ketuntasan minimum 65. Oleh karena itu, subjek penelitian yang dipilih adalah siswa kelas XII MIPA 3 semester ganjil tahun pelajaran 2018/2019 yang berjumlah 40 orang di SMAN 2 Kuta. Objek penelitian ini adalah kemampuan berpikir kreatif matematika siswa pada materi Limit Fungsi Trigonometri. Data kemampuan berpikir kreatif matematika siswa dikumpulkan menggunakan tes uraian matematika dan dianalisis secara deskriptif kualitatif. Penelitian ini dikatakan berhasil jika kemampuan berpikir kreatif matematika siswa minimal kategori kreatif. Setelah dilakukan penghitungan hasil yang diperoleh mengalami peningkatan pada siklus I dan II masing–masing 51,39% dan 71,39%. Jika digolongkan ketingkat kemampuan berpikir kreatif, maka siklus I tergolong cukup kreatif, sedangkan siklus II tergolong kreatif, sehingga tindakan dianggap berhasil. Kesimpulan bahwa penerapan model pembelajaran Group Investigation dapat meningkatkan kemampuan berpikir kreatif matematika.